Parietal relaxation incisions in inguinal hernia surgery - Croci, Fabio; Pérez Penco, Ernesto (Cirugía del Uruguay, 1985)
Parietal relaxation incisions in inguinal hernia surgery constitute a technical recourse that associated with any repair procedure may resu!t in a decrease in recidivation rates. lis basic indica!ion stays with !he treatment of direct hernias and recidivations. Anatomical! y, and procedure lays on sound basis though in a 6% to 10% of cases it misses its physiological target due to special anatomic conformations.